PERBANDINGAN HUKUM INDONESIA DAN MALAYSIA TERHADAP KETIDAKSEIMBANGAN DALAM PERJANJIAN BAKU - Sunarjo Sunarjo (Jurnal Cakrawala Hukum, 2017)
An analysis to the comparison between Indonesian law and Malaysian law toward the imbalance of standard agreement shows that in Indonesia, every agreement or contract must fulfill the requirement of agreement legality as it is arranged in article 1320 KUHP civil. If the requirement is not fulfilled, the agreement law can be cancelled, even the agreement is cancelled for the sake of law. Standard agreement is made unilaterally. The content is more beneficial to the party that makes it (dominant party) and it inflicts a loss upon the party that accepts the agreement (debtor). In Malaysia, agreement and contract are the two different things. Every contract is agreement but not every agreement is as valuable as contract. Contract causes a law implication while agreement does not cause a law implication. Every contract must fulfill a contract character: there is an offer, receipt, reply, intention to realize the legal relation and to be protected by law; ability to make a contract; requirement certainty; and free wish (not being asked or insisted). Standard agreement is arranged in goods selling certificate 1957; it is legally permitted there is a standard article in the standard agreement consisting the limitation of charge guarantee for business doer that inflicts a loss upon the party receiving the contract. Analisis terhadap perbandingan hukum Indonesia dan Malaysia terhadap ketakseimbangan dalam perjanjian baku menunjukkan bahwa di Indonesia setiap perjanjian atau kontrak harus memenuhi syarat sahnya perjanjian sebagaimana diatur dalam pasal 1320 KUHPerdata. Tidak dipenuhinya syarat tersebut berakibat hukum perjanjian dapat dibatalkan, bahkan perjanjian batal demi hukum. Perjanjian baku dibuat secara sepihak. Isinya lebih menguntungkan pihak yang membuat (pihak yang dominan) dan merugikan bagi pihak yang menerima perjanjian (debitur). Di Malaysia antara perjanjian dengan kontrak merupakan dua hal yang berbeda. Setiap kontrak adalah perjanjian tetapi tidak setiap perjanjian bernilai kontrak. Kontrak menimbulkan implikasi hukum sedangkan perjanjian tidak menimbulkan implikasi hukum. Setiap kontrak harus memenuhi karakter kontrak, yaitu ada tawaran, ada penerimaan, ada balasan, niat mewujudkan hubungan yang sah dan dilindungi hukum; kebolehan membuat perjanjian kontrak; kepastian syarat dan terma kontrak; dan kehendak bebas (bukan disuruh atau dipaksa). Perjanjian baku diatur dalam Akta Jualan Barangan 1957 diperkenankan adanya klausula baku dalam perjanjian baku yang berisi pembatasan tanggung gugat pelaku usaha, yang sangat merugikan bagi pihak yang menerima kontrak.